Mechanism Design and Motion Analysis of a Flapping-Wing Air Vehicle. (4th March 2022) - Shi, Yunde; He, Wang; Guo, Mingqiu; Xia, Dan; Luo, Xiang; Ji, Xiaoqiang
Abstract : Micro flapping-wing air vehicles (FWAV) are highly appreciated by scientists and scholars around the world due to their small size, high flexibility, and better manoeuvrability. There are huge potential applications of flapping-wing robots in rescue, survey, and search, as they can enter more dangerous and narrow spaces to accomplish tasks that were previously impossible for people. In this paper, we first analyze the flapping motion of birds by reviewing a large amount of information and literature and identifying the sources of lift and thrust during flight. Then, the double crank and double rocker mechanisms are optimized as the flapping mechanism. Proper flapping-wing size is further determined by analyzing the relative position between the driving mechanism and the flapping mechanism. Moreover, a pitch mechanism consisting of ball hinges is designed to realize the wing's pitching motion for additional thrust. The fuselage and landing gear of the flapping-wing robot are designed for low air resistance and lightweight, and the tail mechanism are designed to have both roll and pitch freedoms, offering excellent manoeuvrability during flight. Simulation results show positive lift force is generated based on the novel pitching design for the small wing. The research in this paper is an important resource for novice researchers to design and study the advanced and complex problems of flapping-wing air vehicles.